Distinct repair processes produce APOBEC-induced deletions, tandem substitutions, and complex mutations in yeast and human cells - Alexandra Puzon; Atri Raval; Cameron Cordero; Daniel Schiefen; Piotr A. Mieczkowski; Steven A. Roberts; Tony M. Mertz (Proceedings of the National Academy of Sciences, 2026)
APOBEC3A (A3A) and APOBEC3B (A3B) induce single base substitution signatures SBS2 and SBS13, which are composed of C>T and C>G mutations, respectively, at T C W sequences in >50% of sequenced tumors. However, few driver mutations have been attributed to APOBEC-induced SBS mutations. Although SBS2 and SBS13 have been associated with additional mutation types, the contribution of APOBECs to non-SBS mutations and the mechanisms that generate noncanonical APOBEC-induced mutations are uncharacterized. Here, we show that A3A expression generates non-SBS mutations including C deletions within TT C motifs, CC>TT and T C >AT/CT/GT dinucleotide variants (DNVs), distinct classes of paired SNV-SNV events, and complex insertion-SBS mutations in a yeast model system. Furthermore, we found that endogenous APOBEC expression in breast cancer cell lines is a significant driver of all these mutation types. In addition, we show that C deletions and complex insertion-SBS mutations within TT C motifs occur primarily by strand slippage during translesion synthesis (TLS) bypass of APOBEC-induced, UNG-dependent, abasic sites. Additionally, we found that CC>TT and T C >AT/CT/GT DNVs, which comprise the APOBEC-associated DBS11 signature, are generated by dU templating and TLS bypass of APOBEC-induced abasic sites, respectively. We also present data indicating that phased APOBEC-induced SNV-SNV mutations are produced during abasic site bypass by TLS. Analysis of WGS data from cultured human cells and tumors indicates that similar mechanisms generate these noncanonical APOBEC-induced mutations in human cancers, providing additional means by which APOBECs could contribute to carcinogenesis and therapeutic resistance.